Disentangling Metaphor from Context: An ERP Study - Bambini, Valentina; Bertini, Chiara; Schaeken, Walter; Stella, Alessandra; Di Russo, Francesco (Frontiers in Psychology, 2016)
A large body of electrophysiological literature showed that metaphor comprehension elicits two different event-related brain potential responses, namely the so-called N400 and P600 components. Yet most of these studies test metaphor in isolation while in natural conversation metaphors do not come out of the blue but embedded in linguistic and extra-linguistic context. This study aimed at assessing the role of context in the metaphor comprehension process. We recorded EEG activity while participants were presented with metaphors and equivalent literal expressions in a minimal context (Experiment 1) and in a supportive context where the word expressing the ground between the metaphor's topic and vehicle was made explicit (Experiment 2). The N400 effect was visible only in minimal context, whereas the P600 was visible both in the absence and in the presence of contextual cues. These findings suggest that the N400 observed for metaphor is related to contextual aspects, possibly indexing contextual expectations on upcoming words that guide lexical access and retrieval, while the P600 seems to reflect truly pragmatic interpretative processes needed to make sense of a metaphor and derive the speaker's meaning, also in the presence of contextual cues. In sum, previous information in the linguistic context biases toward a metaphorical interpretation but does not suppress interpretative pragmatic mechanisms to establish the intended meaning.